Obesity and periodontal disease: literature review - Loyola Livias, Danilo (2023)
Periodontal disease has been studied for years in order to understand its etiology and the different factors that can influence it. On the other hand, obesity is another characteristic that has increased its prevalence in recent decades. The WHO in 2016 estimated the prevalence of 39% of obese adults worldwide. These figures are alarming and are expected to increase in the coming years. In the last decade, multiple studies have emerged showing the relationship between obesity and periodontal disease. Periodontal disease is related to obesity since both have several characteristics in common. The most studied is the inflammatory expression, where cytokines, TNF and Interleukin are elevated at a systemic level, generating negative effects on the oral health status of obese patients.Therefore, long-term studies are required to continue providing more information to understand the relationship between these pathologies and the damage they cause to oral health over time. The present article aims to review the relationship between obesity and periodontitis in the literature.